Pengaruh Pemberian Rebusan Daun Kelor Terhadap Penurunan Tekanan Darah Pada Lansia Penderita Hipertensi di Desa Meunasah Papeun Kecamatan Krueng Barona Jaya Kabupaten Aceh Besar - Rauldah Rauldah; Fauziah Fauziah; Nurul Amna (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Hypertension is categorized as one of the most widespread chronic non-infectious conditions among the elderly and can heighten the risk of serious complications. A non-pharmacological strategy that may be implemented to manage hypertension is the administration of boiled moringa leaves (Moringa oleifera), which are known among scientific communities for possessing antioxidant agents and potent bioactive molecules that function synergistically in maintaining cardiovascular stability and decreasing arterial pressure. This empirical study sought to examine how far the intake of boiled moringa leaves contributes to reducing blood pressure values in hypertensive older adults living within Meunasah Papeun Village, situated in Krueng Barona Jaya Subdistrict, Aceh Besar District. The statistical evaluation showed a significant p-value of 0.001 (p < 0.05), confirming a substantial effect under a quantitative quasi-experimental approach applying the One Group Pretest-Posttest model. The research sample included 20 participants chosen from a total population of 77 individuals through purposive sampling. The investigation took place from May 27 to June 25. Data were obtained using observation forms, standard operating procedures (SOP) for moringa leaf preparation, and manual sphygmomanometer readings. The findings revealed that prior to the application of treatment, the mean systolic blood pressure reached a level of 193.30 mmHg, whereas following the intervention it displayed a considerable decrease, it fell to 129.75 mmHg. The mean diastolic pressure also exhibited a decrease from 94.00 mmHg, confirming the notable influence of moringa leaf decoction in controlling hypertension. In summary, moringa leaf infusion proved effective in lowering blood pressure among elderly individuals suffering from hypertension. It is recommended that patients regularly consume boiled moringa leaves when experiencing increased blood pressure, that community health services provide education regarding non-pharmacological hypertension management through moringa leaf decoction, and that further research explore this topic with broader variables.